Diseño de una red inalámbrica basada en el estándar IEEE 802.11 que opere en la banda de 5 [GHz] y con la cual un ISP pueda comercializar los servicios de acceso a internet en la parroquia veloz de la ciudad de Riobamba - Layedra Ramírez, Marcelo Gustavo (2016)
This project introduces the engineering concepts to design and build networks based in the IEEE 802.11 standard. Due to that WI-FI is one of the most evolved wireless technologies because It works with the most widespread protocols and there is great variety of indoor and outdoor solutions, so It which reached great popularity and acceptance whith WISP in our country. In situations where it is not feasible to implement FTTH networks, companies have the option of this technology to drive the deployment of data access networks throughout the country and make easier the Internet access in our country, thus reducing the digital divide. Because 802.11 has the following features: interoperability, allowing not being tied to a single manufacturer, scalability, which is the ability to expand the network at a low cost of implementation according to demand and work with data speeds of around 400 [Mbps].